(untitled) (Archives of Criminology, 2024)
In recent decades, global mobility control and digital surveillance measures have increasingly prioritised affective aspects and perception-based policies. However, these practices encounter resistance, particularly in the everyday use of connected migrants. Through qualitative data analysis within the tradition of critical surveillance studies, this paper investigates how marginalised mobile groups – often labelled suspects of terrorism and organised crime – circumvent mobile surveillance and social sorting mechanisms within and beyond Fortress Europe. Rising tech literacy and surveillance awareness among users challenge digital policing, reshaping interactions between suspected newcomers and border control authorities. While existing studies focus on countersurveillance activities, less attention is given to strategic “silences” and social filters used to evade profiling and sorting mechanisms, protecting those who fear the risks of crossing a border. Based on notions of secure connectivity, this research employs a multi-site analysis of refugee polymedia use to examine countersurveillance strategies and digital self-censorship practices in transit countries.